Development of sugar palm yarn and woven glass fibre-reinforced unsaturated polyester composites - Norizan, Mohd Nurazzi (2018)
This research was carried out to produce a composite material from sugar palm (Arengga Pinnata) yarn fibre as fibre reinforcement onto unsaturated polyester composites. Analysis of the curing characteristic of unsaturated polyester resin, the structural and morphological characteristics of sugar palm fibre, tensile strength of single sugar palm fibre and interfacial shear stress (IFSS) were studied. The gel time was decreased by up to 36% when 0.05% cobalt solution was used. Alkaline treatment using sodium hydroxide (NaOH) led to the enhancement of the single fibre tensile strength and the IFSS due to the internal morphological changes of the sugar palm fibres. The physical properties (water absorption, density and void content determination), mechanical properties (tensile, flexural, impact and compression), thermal (DMA and TGA) and morphological (SEM) properties of different sugar palm yarn fibre loadings from 10 to 50 wt.% composites was studied, followed by different orientations of fibres (45° and 90°) reinforced composites. From the experiment results, the percentage of water absorption increased as the sugar palm yarn fibre loading increased and reached the equilibrium of absorption on day 12. Increasing trends in the performance of tensile strength and flexural properties were shown for the yarn fibre loadings of up to 30 wt.%. However, a maximum impact strength and compression properties were achieved at 40 wt.% fibre loading. The thermal stability of the composites decreased as the fibre loading increased. The composites with 30 wt.% of fibre loading and 0° fibre orientation exhibited maximum tensile and flexural properties, respectively. While maximum impact and compression properties found at 40 wt.%, respectively. The experiment found the effect of treated sugar palm yarn fibre loading reinforced unsaturated polyester composites with 1% alkaline solutions decreased the physical, mechanical and thermal properties compared to the composites reinforced with untreated sugar palm yarn fibre. This is due to different interaction of single fibre and yarn fibre which affects the interfacial adhesion between the fibre with the matrix. The final 30 wt.% and 40 wt.% of fibres as reinforcement were chosen for the hybridisation studies. Then, the ratio of reinforcement between the sugar palm yarn fibre and woven glass fibre was selected at 70/30, 60/40 and 50/50 wt.%, respectively, which equal to the volume of the mould. The physical, mechanical and thermal properties of the treated sugar palm yarn fibre hybrid composites were found to increase as the glass fibre loading increased up to 50/50 wt.% of fibre ratio for both 30 wt.% and 40 wt.% of fibre loadings. This is due to better interfacial bonding and better chemical interaction between the sugar palm fibre, glass fibre and unsaturated polyester resin as matrix. The improvement on the mechanical and thermal properties also contributed by the synergistic effect from the addition of glass fibre loadings. Hence, the study findings will pave the way towards a greater usage of sugar yarn fibre as a reinforcement for the structural applications such as anti-roll bar in automotive industry, bicycle frame and furniture.